If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 1 = 10 + -5x Reorder the terms: 1 + 8x = 10 + -5x Solving 1 + 8x = 10 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 1 + 8x + 5x = 10 + -5x + 5x Combine like terms: 8x + 5x = 13x 1 + 13x = 10 + -5x + 5x Combine like terms: -5x + 5x = 0 1 + 13x = 10 + 0 1 + 13x = 10 Add '-1' to each side of the equation. 1 + -1 + 13x = 10 + -1 Combine like terms: 1 + -1 = 0 0 + 13x = 10 + -1 13x = 10 + -1 Combine like terms: 10 + -1 = 9 13x = 9 Divide each side by '13'. x = 0.6923076923 Simplifying x = 0.6923076923
| 3/4[8t-12]=6(t-1) | | 2x-5x=y | | a+bi+6(a-bi)=7 | | 27rst+27tsr= | | 3/4[8t-12]=6(1-1) | | 13+-7-10x=2 | | -5b=25 | | 12*90= | | 5+2(x-2)=18 | | v+3=-1 | | 9/4t^-1 | | (-4)(u+2)=((3)(2u+4))+4 | | 10=-4v-v | | [3z-2]+5=9 | | (f/2)-4=1 | | 112+2x=22-4x | | 2[4x+1]-5=1 | | -24=2x-x+6 | | p+9=0 | | 1/2[2x-1]-3=1 | | 9x^5/27x^2 | | 270/3[(4-3)3-(-9)]-53 | | 3(y-2)+2y+5=9y-4+3y+1 | | -132+(-7)=-139 | | k+5=-5 | | -7x-83=29-3x | | x-9y=-39 | | g(x)=-9-5x | | 4x-2+3=7x+x+14 | | 2n-4.5+n=13.5 | | 3.5x-20=2.5x+13 | | 2x-8-4= |